DEPENDENCE OF GRAIN SIZE OF AUSTENITE STEEL OF RAILWAY WHEEL FROM PARAMETERS OF HOT DEFORMATION - Vakulenko, L. I. (Science and Transport Progress, 2015)
Purpose. The estimation of heat temperature influence and degree of hot reduction of carbon steel on the size of grain аustenite at making of railway wheels. Methodology. The material for research was carbon steel, mark 60 with carbon content of 0,55 and 0,65 %, selected from the fragments of railway wheels. The size of grain аustenite depending on a temperature (from 800 to 1 150 ºC) and degrees of hot deformation (10−50 %) was determined. The size of grain was determined under a light microscope with the use of quantitative metallography methods. Findings. The use of cooling in the process of hot reduction of the railway wheel will allow dispergating the structure of аustenite on large distances from the surface of the rim. The reason for this is that the volumes of metal after cooling have an increased strength and will be exposed in less degree to the plastic deformation. To compare the cooling layers near-by with the surface of rim, they are more warmed-up in internal volumes of metal. In the conditions of continuity of plastic deformation distribution, having a high temperature, they will be exposed to the reduction on the large total degree of deformation. In consequence of the resulted decisions more even austenitic structure must be formed on the section of rim of railway wheel. To obtain the effect of disperse grain of аustenite at making of the whole-rolled railway wheels it is necessary to decrease the heat temperature of billet under rolling or increase the degree of reduction on the lasts stages of shape-generating deformation. The pause by duration of 1,5 min. after reduction of 20 % at a temperature 950 ºC is sufficiently for processes completion of dynamic and static recrystalization of аustenite carbon steel of the railway wheel. Originality. Increase of plastic deformation degree, especially in the central volumes of rim is accompanied by the decrease of heterogeneity of austenitic structure on his section. The mechanism of disperse structure of аustenite is based on slow down of development processes of recrystallization in carbon steel at the metal reduction temperature decrease of elements in the railway wheel when they are formed on a rolling mill. Practical value. Temperature decrease of hot reduction of billets in the conditions of flatting mill from 1240−1260 ºC to 1 150 ºC is accompanied by decrease of size grain of аustenite from a 0−1 mark to 2−5 in the different elements of the railway wheel.